Microstructure Observation of Naturally Aged Thixoforming ZA27 Alloy - Chen,Ti Jun (2015)
The microstructure of the thixoformed ZA27 alloy naturally aged for 5 years has been observed and analyzed. The results indicate that most of the original β + η laminar eutectics have changed into the structures that small α particles uniformly distribute in η phase matrix. Both the β phase and α’ phase have also decomposed. It is suggested that a continuous or dot-line α phase first precipitates in the β phase close to the eutectic η phase layer. Then eutectoid η phase nucleates or directly grows up from the eutectic η phase, which promotes the nucleation of eutectoid α phase or the direct growth of the α phase from the existing α phase. Subsequently, the resulting α + η phases grow towards the β phase inside, forming the regular laminar α + η structures. The laminar structures always continuously grow across the center α’ phase, which leads the α’ phase also to transform into regular α + η laminar structures. The laminar structures may crack possibly due to internal stress. The eutectoid η phase lamellae have a tendency of changing from laminar shape to particle form, resulting in the formation of non-laminar structures.